2022
DOI: 10.1101/2022.02.20.481201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Keratinocyte-Associated Protein 3 is a novel gene for adiposity with differential effects in males and females

Abstract: Objective: Despite the obesity crisis in the United States, the underlying genetics are poorly understood. Our lab previously identified Keratinocyte-associated protein 3, Krtcap3, as a candidate gene for adiposity where increased expression of Krtcap3 correlated with decreased fat mass. Here we seek to confirm that Krtcap3 expression affects adiposity traits. Methods: We developed an in vivo whole-body Krtcap3 knock-out (KO) rat model. Wild-type (WT) and KO rats were placed onto a high-fat or low-fat diet at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 30 publications
2
9
2
Order By: Relevance
“…This could be explained by the fact that serum CORT increased only in the KO rats as opposed to WT, in contrast to our previous work where CORT was higher in the WT rats (Szalanczy et al, 2023). Although we are unable to make direct comparisons between the studies, that decreased expression of Krtcap3 leads to increased eating and adiposity under conditions of chronic stress is consistent with the previous findings (Szalanczy et al, 2022;Szalanczy et al, 2023) and further supports a role of Krtcap3 in the stress response. Whether the role of Krtcap3 in the stress response is protective or deleterious, however, is still an open question and future studies will be needed to address this.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This could be explained by the fact that serum CORT increased only in the KO rats as opposed to WT, in contrast to our previous work where CORT was higher in the WT rats (Szalanczy et al, 2023). Although we are unable to make direct comparisons between the studies, that decreased expression of Krtcap3 leads to increased eating and adiposity under conditions of chronic stress is consistent with the previous findings (Szalanczy et al, 2022;Szalanczy et al, 2023) and further supports a role of Krtcap3 in the stress response. Whether the role of Krtcap3 in the stress response is protective or deleterious, however, is still an open question and future studies will be needed to address this.…”
Section: Introductionsupporting
confidence: 80%
“…We previously generated a whole-body in vivo Krtcap3-KO on the WKY (WKY/NCrl; RGD_1358112) inbred rat strain (WKY-Krtcap3 em3Mcwi ) and established a breeding colony at Wake Forest University School of Medicine (WFUSOM) in 2019 (Szalanczy et al, 2022). At Building A of WFUSOM, rats were housed in ventilated cages (46 cm × 24 cm × 20 cm) at 22 °C in a 12 h light/dark cycle (dark from 18:00 to 6:00) at standard temperature and humidity conditions, and given ad libitum access to water.…”
Section: Animalsmentioning
confidence: 99%
“…This is consistent with the negative correlation between Krtcap3 liver expression and associated phenotypes ( R p ~ −0.25 – Figure 4C ), suggesting that the WKY haplotype increases the expression of liver Krtcap3 leading to reduced accumulation of fat pad and TRIG. We have recently shown that Krtcap3 knock-out rats exhibit increased body weight, with female rats showing increased fat pad weights and insulin sensitivity [32], thereby validating this gene. Several additional genes were identified as partial mediators, with different genes acting in adipose vs liver ( Table 2 ), indicating multiple causal genes may underlie this locus.…”
Section: Resultsmentioning
confidence: 99%
“…Krtcap3 does not fall within human GWAS loci for BMI or WHR, but has been identified as a pleiotropic gene for obesity, dyslipidemia and type 2 diabetes using a multi-variate analysis [43]. Recent work by our group confirmed Ktrcap3’ s role in adiposity using a rat Krtcap3 knock-out; both male and female knock-out rats have increased body weight, with females showing increased adiposity and insulin sensitivity [32]. Interestingly, Krtcap3 is unlikely the only gene acting in this locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation